2015
DOI: 10.18488/journal.87/2015.2.2/87.2.27.38
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyamines and Diseases: Reducing Polyamine Intake Can Be Beneficial In Cancer Treatment

Abstract: Polyamines are most abundant polycationic natural amines and involved in several physiological processes. Contribution/ OriginalityThis study contributes in the existing literature by providing a detailed information on the importance of dietary polyamines in health and diseases. This study also highlights the beneficial impact of low polyamine diet on cancer treatment, and helps to increase awareness of daily polyamine intake regarding individual requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…There are three ways to maintain the PA pool in the body: intestinal microorganisms, de novo biosynthesis (endogenous), and supply through diet (exogenous). These mechanisms simultaneously regulate the synthesis, catabolism, and transport of intracellular PA concentration [ 34 ]. However, the exogenous diet provides the maximum quantity of PAs than the process of endogenous biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three ways to maintain the PA pool in the body: intestinal microorganisms, de novo biosynthesis (endogenous), and supply through diet (exogenous). These mechanisms simultaneously regulate the synthesis, catabolism, and transport of intracellular PA concentration [ 34 ]. However, the exogenous diet provides the maximum quantity of PAs than the process of endogenous biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exogenous diet provides the maximum quantity of PAs than the process of endogenous biosynthesis. Hence, PAs in nutrition (dietary polyamines) play a crucial role in maintaining the biosynthesis of PAs because distortion in the metabolism of PAs may lead to several health disorders [ 34 ]. Various food items contain the required amounts of PAs, i.e., plant-derived foods have mostly PUT and SPD, and meat products mainly contain SPE, while dairy products are rich in SPD and PUT [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding polyamines, their concentration (putrescine, cadaverine, spermidine, and spermine) in organs and tissues depends on their endogenous production and oxidation rates and their intake from foods [ 26 ]. Dietary polyamines may be harmful, neutral, or beneficial, depending on the specific polyamine involved and disease [ 27 ]. In this context, a positive or detrimental effect has been reported for yogurt consumption depending on the cancer type and bacterial strains used in the manufacture of yogurt; evidence supports the potential role of consumption of probiotic yogurt in the reduction of colorectal cancer risk in healthy adults [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, limited suggestive evidence has shown that yogurt consumption increases the risk of prostate and kidney cancers in a dose-dependent manner in healthy adults, although this effect is not associated with the calcium content in yogurt [ 32 , 33 , 34 ]. Increased risk to develop these cancers types has been attributed to the polyamines content in dairy products [ 27 ], since they (putrescine and spermidine) are the other principal biogenic amines in yogurts [ 20 , 35 ], including goat’s milk yogurts [ 21 , 22 ]. Indeed, cadaverine, spermidine, and spermine present in conventional yogurts (1.9 to 2.8 µmol) were entirely absorbed by the human intestine, being yogurt suggested as a relevant source of polyamines for the organism [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation